Human gesture to restore nature : a success story - Gadgil, Medha (Pune Forest Department Govt. of Maharashtra, 2018)
This book talks about the success story of sardar sarovar (narmada ) project and a human gesture to restore nature.
Sardar Sarovar (Narmada) project
Keywords: IAS as an author; Environment management; Sustainable development